A new context for ethics education objectives in a college of business: Ethical decision-making models - Herndon, Neil C. (Journal of business ethics, 1996)
Objectives for ethics education in business school courses generally appear to be based on custom, intuition, and judgment rather than on a more unified theoretical/empirical base. These objectives may be more clearly implemented and their effects studied more rigorously if they could be rooted in the components of ethical decision-making models shown to be influential in ethical decision making. This paper shows how several widely used ethics education objectives can be placed in the context of current models of ethical decision making.